Participative Design in Irkutsk - Repina, Anastasia (project baikal, 2018)
The article reviews public discussion of the projects for public spaces in four districts of Irkutsk. The key aspects of the project “Formation of a comfortable urban realm” are presented. The article also features the peculiarities of the public discussion of the projects among different groups of citizens and in different districts of Irkutsk.